2008
DOI: 10.1590/s1676-06032008000200007
|View full text |Cite
|
Sign up to set email alerts
|

Anurofauna de remanescentes de floresta Atlântica do município de São José do Barreiro, estado de São Paulo, Brasil

Abstract: In the studied period, we registered 35 anuran species in nine families. The anuran richness observed in the studied region is similar to other localities considered preserved, as the Estação Ecológica Juréia-Itatins (Peruíbe, SP) and Serra do Japi (Jundiaí-SP). The similarity in species composition among seven localities in Atlantic Forest in São Paulo state was associated to the vegetal types of the studied areas. The ample altitude variation, the presence of different types of vegetation, and the little kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
2
8
1
5
Order By: Relevance
“…In the wetland zones, the dominant species was Scinax fuscomarginatus (Table 3). This small-sized hylid is commonly associated with reeds and other emergent plants in temporary ponds and lagoons (Brasileiro et al 2005, Van-Silva et al 2007, Serafim et al, 2008, similar to those observed in the wetlands of the study area ( Figure 2B, D), except for the SU P4. This SU differed from the others by not showing plant stratification, being essentially characterized as a temporary pond in sandy soil the surroundings of which were covered by grasses ( Figure 2C).…”
Section: Discussionsupporting
confidence: 69%
“…In the wetland zones, the dominant species was Scinax fuscomarginatus (Table 3). This small-sized hylid is commonly associated with reeds and other emergent plants in temporary ponds and lagoons (Brasileiro et al 2005, Van-Silva et al 2007, Serafim et al, 2008, similar to those observed in the wetlands of the study area ( Figure 2B, D), except for the SU P4. This SU differed from the others by not showing plant stratification, being essentially characterized as a temporary pond in sandy soil the surroundings of which were covered by grasses ( Figure 2C).…”
Section: Discussionsupporting
confidence: 69%
“…Haddad and Prado 2005), which were habitats poorly sampled in our study. Since our sampling effort was concentrated in high altitude areas, widely distributed species, such as Hypsiboas faber, Leptodactylus labyrinthicus, and Leptodactylus mystacinus and also those known to occur in lower altitude areas (Serafim et al 2008) were not recorded. The specific locality in which Bokermann (1972) found B. clepsydra, andGiaretta et al (1993) found M. bocainensis, called Campo de Friticultura (also known as Fazenda Ponte Alta) was surveyed for 14 consecutive months.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of amphibian and reptile diversity in Atlantic Rainforest areas have grown considerably over the past five years (e.g., Dixo and Verdade, 2006;Juncá, 2006;Moraes et al, 2007;Colombo et al, 2008;Carvalho-e-Silva et al, 2008;Lucas and Fortes, 2008;Santana et al, 2008;Serafim et al, 2008;Bertoluci et al, 2009;Narvaes et al, 2009;Marques et al, 2009;Araujo et al, 2010;Wachlevski and Rocha, 2010;Costa et al, 2010;Sousa et al, 2010;Vilela et al, 2011). For example, the number of studies concerning the composition of local amphibian and reptile fauna have also increased in this period in the state of Rio de Janeiro (e.g., Rocha and Van Sluys, 2006;Carvalho et al, 2007;Carvalho-e-Silva et al, 2000;Rocha et al, 2008;Silva et al, 2008;Pontes et al, 2009;Almeida-Gomes et al, 2008.…”
Section: Introductionmentioning
confidence: 99%